Spinal modulations accompany peripheral fatigue during prolonged tennis playing - Girard, O.; Racinais, S.; Micallef, J. P.; Millet, G. P. (Scandinavian Journal of Medicine & Science in Sports, 2011)
To examine the time course of alteration in neural process (spinal loop properties) during prolonged tennis playing, 12 competitive players performed a series of neuromuscular tests every 30 min during a 3-h match protocol. Muscle activation (twitch interpolation) and normalized EMG activity were assessed during maximal voluntary contraction (MVC) of plantar flexors. Spinal reflexes and M-waves were evoked at rest (i.e., Hmax and Mmax, respectively) and during MVC (i.e., Hsup, V-wave, Msup, respectively). MVC torque declined significantly (P<0.001) across the match protocol, due to decrease (P<0.001) in muscle activation and in normalized EMG activity. The impairment in MVC was significantly correlated (r=0.77; P<0.05) with the decline in muscle activation. Hmax/Mmax (P<0.001), Hsup/Msup (P<0.01) and V/Msup (P<0.05) ratios were depressed with fatigue and decreased by ?80%, 46% and 61% at the end of exercise, respectively. Simultaneously, peak twitch torque and M-wave amplitude were significantly (P<0.01) altered with exercise, suggesting peripheral alterations. During prolonged tennis playing, the compromised voluntary strength capacity is linked to a reduced neural input to the working muscles. This central activation deficit partly results from a modulation in spinal loop properties.